Anti-fungal potentials of extracellular metabolites of western ghats isolated streptomyces sp NII 1006 against moulds and yeasts - Jayamurthy, Himani; Sajna, Kuttavan Valappil; Dastager, Syed Gulam; Pandey, Ashok (Indian Journal of Experimental Biology, 2014)
Realization of hazardious effects of chemical fungicides has led to an interest in the usage of biocontrol agents. The present study, therefore, evaluates the biocontrol efficacy of Western Ghats (India) soil bacterial isolates. A potential strain NII 1006 was evaluated for its antagonistic property against a diverse range of moulds and yeasts. The strain was characterized morphologically, biochemically and molecularly, which revealed the isolate belonged to Streptomyces genus. Organic solvent extracts of NII 1006 culture filtrates inhibited the growth of the test pathogens indicating that growth suppression was due to extracellular anti-fungal metabolites present in the culture filtrates. The strain produced extracellular chitinase enzyme in addition to some stable partially purified anti-fungal compounds. Morphological changes such as hyphae degradation into debris and abnormal shapes were observed in test fungi and yeast grown on potato dextrose broth that contained the NII 1006 culture filtrate. The cell free supernatant has a tolerance to wide range of pH, temperature and enzymes such as lipase and protease. The biocontrol potential of NII 1006 strain may be correlated significantly with their ability to produce antibiotics as well as extracellular hydrolytic enzymes particularly chitinolytic enzyme.
Keywords: Anti-fungal activity; Biocontrol; Extracellular anti-fungal metabolites; Streptomyces